Методика измерения социальной солидарности в украинском обществе. Проверка теории с помощью метода моделей линейных структурных уравнений - Урсуленко, К. (Iнститут соціології НАН України, 2009)
Recent studies on social solidarity have been concentrated either on the theoretical exploration of the phenomenon or on the investigation of solidarity aspects in empirical studies of little social groups. The paper presents a theory of social solidarity and a measurement instrument to study the phenomenon on the general level of Ukrainian society. The author provides the description of methodic issues as well as analysis strategy and interpretation framework. Based on the data provided by Institute of Sociology in Kiev three different indices are computed to describe normative and structural aspects of social solidarity. Using structural equation modeling the relationships between concepts of the theory are specified and explained.